Bridge the Gap: Reducing Inequity in Hospital Readmissions for African American Patients with Heart Failure Through Quality Improvement Initiatives (Mary Ann Liebert, 2021)
Purpose: Heart failure (HF) disproportionately impacts African Americans. We evaluated existing quality improvement (QI) initiatives and patient and provider perceptions of barriers to HF care to develop equity-centered QI recommendations. Methods: We performed a literature review, interviewed providers and patients (N=11), and conducted a root cause analysis at a safety net hospital in San Francisco, California. Results: We have identified four elements to foster a more equitable HF care model: screening for social determinants of health, technological innovation, optimization of space, and implicit bias training. Conclusion: QI initiatives for HF should integrate health equity elements in their design and implementation.